IMPLIKASI HUKUM HUMANITER INTERNASIONAL DALAM KONFLIK ISRAEL PALESTINA MELALUI ANALISIS KRITIS ATAS DAMPAK TERHADAP SIPIL DAN PENEGAKAN HUKUM GLOBAL - M. Imam Zulfikar; Aromarika D. Sukoco,Tarsius Susilo, Agustinus Adi Santoso, Muhammad Taufik Zega (JOURNAL OF LAW AND NATION, 2025)
The armed conflict between Israel and Palestine stands as one of the longest and most complex in modern history, presenting substantial challenges for the application of International Humanitarian Law (IHL). This prolonged conflict not only inflicts profound suffering on civilians from both sides but also raises critical questions regarding the effectiveness and impartiality of wartime legal frameworks in politically charged global contexts. This article critically examines the implementation or omission of fundamental IHL principles such as distinction, proportionality, and military necessity by key actors in the conflict. Furthermore, it assesses the legal and humanitarian impacts on vulnerable civilian populations, particularly women and children, who bear the brunt of armed hostilities. Using a normative and document-based approach, supported by analysis of international reports from the UN, Human Rights Watch, and the International Criminal Court (ICC), this article highlights structural weaknesses in law enforcement mechanisms and exposes political biases that obstruct justice. The findings indicate the need for reforms in global accountability systems and strengthened legal jurisdiction over serious violations. This study aspires to contribute significantly to the discourse on international legal standards and support more equitable protection of human rights in ongoing armed conflicts.